Not all estimators are born equal: The empirical properties of some estimators of long memory - Rea, W.; Oxley, Leslie; Reale, M.; Brown, J. (2012)
We present the results of a simulation study into the properties of 12 different estimators of the Hurst parameter, H, or the fractional integration parameter, d, in long memory time series which are available in R packages. We compare and contrast their performance on simulated Fractional Gaussian Noises and fractionally integrated series with lengths between 100 and 10,000 data points and H values between 0.55 and 0.90 or d values between 0.05 and 0.40. We apply all 12 estimators to the Campito Mountain data and estimate the accuracy of their estimates using the Beran goodness-of-fit test for long memory time series. © 2012 IMACS.